Comparison of the Accuracy of HSV1 and HSV2 Antibody Tests with PCR in the Diagnosis of Recurrent Genital Herpes - Deng J; Ye YJ; Chen QP; Zhang YJ; Liu JF (Dove Medical Press, 2024)
Jia Deng, Yu-Jian Ye, Qiu-Ping Chen, Yi-Jin Zhang, Ji-Feng Liu Department of Dermatology, Hangzhou Third People's Hospital, Hangzhou, People's Republic of ChinaCorrespondence: Ji-Feng Liu, Department of Dermatology, Hangzhou Third People's Hospital, No. 38 of West Lake Road, Shangcheng District, Hangzhou, Zhejiang, 310009, People's Republic of China, Tel/Fax +86 0571-87827514, Email fliu8166@126.comObjective: To assess the accuracy of HSV1and HSV2 antibody testing in identifying genital herpes infection.Methods: A cohort of 299 patients previously diagnosed with recurrent genital herpes, confirmed via PCR, were tested using ELISA for HSV1 and HSV2 IgM and IgG antibodies. The study compared the accuracy of HSV1 and HSV2 antibody tests in diagnosing genital herpes.Results: Among 299 patients, 14 tested positives for HSV1 DNA. Of these, 9 had HSV1 IgG antibodies, but none had HSV2 IgG antibody. Among 278 patients with HSV2 DNA, 149 had HSV1 IgG, 9 had HSV2 IgG, and 97 had both. Seven patients had both HSV1 and HSV2 DNA; 3 had HSV1 IgG, 1 had HSV2 IgG, and 3 had both. The accuracy of HSV1 IgG for HSV1 infection was 64.2%, and for HSV1 and HSV2 co-infection, 85.7%. The accuracy of HSV2 IgG for HSV2 infection was 38.1%, and for HSV1 and HSV2 co-infection, 57.1%. The combined antibody positivity accuracy was 34.9%.Conclusion: Genital herpes is primarily caused by HSV2 (92.98%). A smaller percentage is HSV1 (4.67%) or co-infection (2.34%). Despite relatively low diagnostic accuracy (34.9- 85.7%) for antibody detection, combined antibody testing is necessary. Herpes DNA testing is recommended for accurate diagnosis. Absence of antibodies does not rule out genital herpes and clinical assessment is essential.Keywords: antibody test, DNA test, genital herpes, HSV-1, HSV-2